Algoritma Promethee II Dalam Seleksi Anggota Paskibra Baru Pada SMA Negeri 4 Pematangsiantar - Guntur, Azi; Damanik, Irfan Sudahri; Fauzan, M (STIKOM Tunas Bangsa Pematangsiantar, 2021)
This study aims to conduct selection in determining the members of the New Paskibra in Pematangsiantar Public High School 4 engaged in the field of Education. Besides being based on ability, the addition of several variables and assessment indicators in the form of health variables, height, whether there is togetherness, organizational participation and so on are expected to be able to provide a clearer picture of the criteria of new Paskibra Members in Pematangsiantar 4 Public High School, especially in the best Paskibra Member data which is ambiguous. In this thesis the Promethee II method is a method implemented for determining the criteria for new post-members members and is one of the multi-criteria decision-making methods based on the concept of outranking using pairwise comparisons of alternatives based on each appropriate criterion